The Best Argument against God - Oppy, G. author. aut Link
VI, 93 p.
Keywords: .... compares two theories—Naturalism and Theism—on a wide range of relevant data. It concludes that Naturalism should be preferred to Theism on that data. The central idea behind the argument is that, while Naturalism is simpler than Theism, there is no relevant data that Naturalism fails to explain at least as well as Theism does.